Untargeted metabolomics confirms and extends the understanding of the impact of aminoimidazole carboxamide ribotide (AICAR) in the metabolic network of Salmonella enterica - Jannell V. Bazurto; Stephen P. Dearth; Eric D. Tague; Shawn R. Campagna; Diana M. Downs (Microbial Cell)
In Salmonella enterica, aminoimidazole carboxamide ribotide (AICAR) is a purine biosynthetic intermediate and a substrate of the AICAR transformylase/IMP cyclohydrolase (PurH) enzyme. When purH is eliminated in an otherwise wild-type strain, AICAR accumulates and indirectly inhibits synthesis of the essential coenzyme thiamine pyrophosphate (TPP). In this study, untargeted metabolomics approaches were used to i) corroborate previously defined metabolite changes, ii) define the global consequences of AICAR accumulation and iii) investigate the metabolic effects of mutations that restore thiamine prototrophy to a purH mutant. The data showed that AICAR accumulation led to an increase in the global regulator cyclic AMP (cAMP) and that disrupting central carbon metabolism could decrease AICAR and/or cAMP to restore thiamine synthesis. A mutant (icc) blocked in cAMP degradation that accumulated cAMP but had wild-type levels of AICAR was used to identify changes in the purH metabolome that were a direct result of elevated cAMP. Data herein describe the use of metabolomics to identify the metabolic state of mutant strains and probe the underlying mechanisms used by AICAR to inhibit thiamine synthesis. The results obtained provide a cautionary tale of using metabolite concentrations as the only data to define the physiological state of a bacterial cell.